Enamel matrix protein derivative plus synthetic bone substitute for the treatment of mandibular Class II furcation defects: a case series - Queiroz, Lucas Araujo; Santamaria, Mauro Pedrine [UNESP]; Casati, Marcio; Silverio, Karina; Nociti Junior, Francisco; Sallum, Enilson (Quintessence Publishing Co Inc, 2015)
Objectives: The aim of this study is to report on the treatment of mandibular Class II furcation defects with enamel matrix protein derivative (EMD) combined with a beta TCP/HA (beta-tricalcium phosphate/hydroxyapatite) alloplastic material. Method and Materials: Thirteen patients were selected. All patients were nonsmokers, systemically healthy, and diagnosed with chronic periodontitis; had not taken medications known to interfere with periodontal tissue health and healing; presented one Class II mandibular furcation defect with horizontal probing equal to or greater than 4 mm at buccal site. The clinical parameters evaluated were probing depth (PD), relative gingival margin position (RGMP), relative vertical clinical attachment level (RVCAL), and relative horizontal clinical attachment level (RHCAL). A paired Student t test was used to detect differences between the baseline and 6-month measurements, with the level of significance of .05. Results: After 6 months, the treatment produced a statistically significant reduction in PD and a significant gain in RVCAL and RHCAL, but no observable change in RGMP. RVCAL ranged from 13.77 (+/- 1.31) at baseline to 12.15 (+/- 1.29) after 6 months, with a mean change of -1.62 +/- 1.00 mm (P<.05). RHCAL ranged from 5.54 (+/- 0.75) to 2.92 (+/- 0.92), with a mean change of -2.62 +/- 0.63 mm (P<.05). After 6 months, 76.92% of the patients improved their diagnosis to Class I furcation defects while 23.08% remained as Class II. Conclusion: The present study has shown that positive clinical results may be expected from the combined treatment of Class II furcation defects with EMD and beta TCP/HA, especially considering the gain of horizontal attachment level. Despite this result, controlled clinical studies are needed to confirm our outcomes.
Keywords: Class II furcation defects; Enamel matrix protein derivative; Periodontal regeneration; Synthetic bone substitute